Inclination of Students towards Active Participation in Extracurricular Activities as an Effective Tool for Professional Development during Education in Pakistan - Abdul Rahman; Rabia Ali Hundal (Universitas Muhammadiyah Surakarta, 2021)
Extracurricular activities (ECA) are, nowadays, considered as an essential part of any school system of any level. The present study reveals the relation of ECA with student’s performance, academic achievements, career selection and, last but not the least, professional development (PD) of students in Pakistan. The re-search was carried out by developing a questionnaire. It consists of five comprehensive questions relating the ECA with PD. The validity and reliability of questions were checked. The research population consisted of students, with some managerial and leadership experience, from different institutes of Pakistan. The sam-ple consist of majorly all the members of the respective population. After purposively selection, the ques-tionnaire was distributed among 110 selected members of populations for research. Response rate was 90.9% as 100 members filled the form and all the responses was considered valid for the statistical study. Different statistical methods were used to carry out the research consisting of standard deviation, arithmetic means etc. It was clearly observed the respondent’s consideration of ECA as tool for PD of students is high. It was also observed that consideration of ECA for cultivation of interpersonal skills is high and same rate was high for ECA’s impact on career selection. In addition to this, the consideration rate of ECA for im-proving of managerial skills and self-efficacy is high. So, it is concluded that educational institutes should motivate their students to participate in ECA for better a career.